2017
DOI: 10.1111/ejn.13606
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of visuomotor adjustments during scaling of human finger movements

Abstract: Visually guided finger movements include online feedback of current effector position to guide target approach. This visual feedback may be scaled or otherwise distorted by unpredictable perturbations. Although adjustments to visual feedback scaling have been studied before, the underlying brain activation differences between upscaling (visual feedback larger than real movement) and downscaling (feedback smaller than real movement) are currently unknown. Brain activation differences between upscaling and downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Among studies that implemented a continuous shift of feedback, six activations were in lobule VI (Brand et al, 2017;Diedrichsen et al, 2005;Grafton et al, 2008;Graydon et al, 2005;Inoue et al, 2000;Zheng et al, 2013), three in lobule VIII (Anguera et al, 2010;Krakauer et al, 2004;Tourville et al, 2008), with two foci just anterior to Lobule VI in the IV/V region (Anguera et al, 2010;Seidler et al, 2006), and two in Crus I/II (Krakauer et al, 2004). The same regions were reported for studies of mismatched feedback, with three foci incorporated in Lobule VI (Pfordresher et al, 2014;Tunik et al, 2013;Yomogida et al, 2010), two in Crus II (Pfordresher et al, 2014;Schnell et al, 2007), and one in Lobule VIII (Pfordresher et al, 2014).…”
Section: Choice Of Feedback Manipulationmentioning
confidence: 61%
See 3 more Smart Citations
“…Among studies that implemented a continuous shift of feedback, six activations were in lobule VI (Brand et al, 2017;Diedrichsen et al, 2005;Grafton et al, 2008;Graydon et al, 2005;Inoue et al, 2000;Zheng et al, 2013), three in lobule VIII (Anguera et al, 2010;Krakauer et al, 2004;Tourville et al, 2008), with two foci just anterior to Lobule VI in the IV/V region (Anguera et al, 2010;Seidler et al, 2006), and two in Crus I/II (Krakauer et al, 2004). The same regions were reported for studies of mismatched feedback, with three foci incorporated in Lobule VI (Pfordresher et al, 2014;Tunik et al, 2013;Yomogida et al, 2010), two in Crus II (Pfordresher et al, 2014;Schnell et al, 2007), and one in Lobule VIII (Pfordresher et al, 2014).…”
Section: Choice Of Feedback Manipulationmentioning
confidence: 61%
“…The anterior map is centered on lobule VI, while the posterior is centered on lobule VIII. The majority of cerebellar activations in studies included in our analyses were reported in lobules VI (Brand et al, ; Diedrichsen et al, ; Grafton et al, ; Graydon et al, ; Inoue et al, ; Pfordresher et al, ; Tunik et al, ; Yomogida et al, ; Zheng et al, ), and VIII (Anguera et al, ; Krakauer et al, ; Pfordresher et al, ; Tourville et al, ). This demonstrates that where cerebellar activations were observed they were not distributed randomly, making these findings unlikely to be false positives.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The anterior map is centred on lobule VI, while the posterior is centred on lobule VIII. The majority of cerebellar activations in studies included in our analyses were reported in lobules VI (Brand et al, 2017;Diedrichsen et al, 2005;Grafton et al, 2008;Graydon et al, 2005;Inoue et al, 2000;Pfordresher et al, 2014;Tunik et al, 2013;Yomogida et al, 2010;Zheng et al, 2013), and VIII (Anguera et al, 2010;Krakauer et al, 2004;Pfordresher et al, 2014;Tourville et al, 2008). This demonstrates that where cerebellar activations were observed they were not distributed randomly, making these findings unlikely to be false positives.…”
Section: Cerebellummentioning
confidence: 82%